Exfoliated graphite-polythiophene composite, its manufacturing method, and corrosion-resistant coating material
A thinning graphite-polythiophene complex addresses the handling issues of toxic alkyl aldehydes by forming a stable, versatile composite that enhances resin and electrode material properties with improved conductivity and mechanical strength.
Patent Information
- Application Number
- JP2021053494
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-26
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2041-03-26
Smart Images

Figure 0007624624000002 
Figure 0007624624000003 
Figure 0007624624000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an exfoliated graphite-polythiophene composite, a method for producing the exfoliated graphite-polythiophene composite, and a corrosion-resistant coating material using the exfoliated graphite-polythiophene composite. [Background technology]
[0002] Conventionally, carbon materials have been widely used as resin reinforcing materials, conductive materials, or thermally conductive materials. In recent years, their use as electrode materials for secondary batteries such as lithium ion secondary batteries and capacitors has been considered. Examples of such carbon materials include graphite, carbon nanotubes, and exfoliated graphite.
[0003] Exfoliated graphite is obtained by exfoliating graphite and is a laminate of graphene or graphene sheets that are thinner than the original graphite. Such exfoliated graphite has a large specific surface area and is excellent in electrical conductivity, gas barrier properties, mechanical strength, etc., and is therefore expected to be applied in a wide range of fields.
[0004] As a method for producing exfoliated graphite, for example, a production method using a graphite intercalation compound (GIC) is known. In this method, an alkali metal is intercalated between the graphene layers of graphite. Then, the graphite is exfoliated by an exfoliation treatment such as ultrasonic treatment or heat treatment. In this way, exfoliated graphite can be obtained.
[0005] Furthermore, Patent Document 1 listed below discloses a method for exfoliating graphite to obtain exfoliated graphite by mixing a GIC in which at least an alkali metal is intercalated between the graphene layers of graphite with an alkylaldehyde. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] International Publication No. 2020 / 175504 Summary of the Invention [Problem to be solved by the invention]
[0007] Incidentally, in the exfoliated graphite obtained by the manufacturing method as in Patent Document 1, an alkyl aldehyde such as decanal is used as a dispersion medium to prevent re-aggregation of graphene. As a result, Patent Document 1 states that even when the exfoliated graphite is dispersed in a resin or a solvent, the exfoliated graphite is unlikely to be folded or curled. However, alkyl aldehydes such as decanal often have biotoxicity, such as irritation to the skin and eyes. In addition, since they are aldehydes, they have the problem of being easily oxidized and having low chemical stability.
[0008] The present invention has been made in consideration of the above-mentioned circumstances, and aims to provide an exfoliated graphite-polythiophene composite that is less likely to be folded or curled and is highly versatile, a method for producing the exfoliated graphite-polythiophene composite, and a corrosion-resistant coating material using the exfoliated graphite-polythiophene composite. [Means for solving the problem]
[0009] The exfoliated graphite-polythiophene composite according to the present invention contains exfoliated graphite, which is a laminate of graphene or graphene sheets, and a polythiophene derivative.
[0010] In a specific aspect of the exfoliated graphite-polythiophene composite according to the present invention, the polythiophene derivative is poly(3-hexylthiophene).
[0011] In another specific aspect of the exfoliated graphite-polythiophene composite according to the present invention, the number of stacked graphene sheets in the exfoliated graphite is 1 or more and 15 or less.
[0012] In still another specific aspect of the exfoliated graphite-polythiophene composite according to the present invention, the surface of the exfoliated graphite-polythiophene composite is modified with a functional group derived from a compound having a carbonyl group, and the exfoliated graphite is a laminate of graphene or graphene sheets, and is composited with a polythiophene derivative.
[0013] In still another specific aspect of the exfoliated graphite-polythiophene composite according to the present invention, the compound having a carbonyl group is an aldehyde derivative.
[0014] In yet another specific aspect of the exfoliated graphite-polythiophene composite according to the present invention, the aldehyde derivative is an alkylaldehyde.
[0015] The method for producing an exfoliated graphite-polythiophene composite according to the present invention is a method for producing an exfoliated graphite-polythiophene composite constructed according to the present invention, and includes the steps of: preparing a graphite intercalation compound in which at least an alkali metal is intercalated between the graphene layers of graphite; mixing the graphite intercalation compound with a compound having a carbonyl group to exfoliate the graphite to obtain exfoliated graphite; and compounding the exfoliated graphite with a polythiophene derivative.
[0016] The corrosion-resistant coating material of the present invention comprises an exfoliated graphite-polythiophene composite constructed according to the present invention. Effect of the Invention
[0017] According to the present invention, it is possible to provide an exfoliated graphite-polythiophene composite that is resistant to folding or curling and has high versatility, a method for producing the same, and a corrosion-resistant coating material using the exfoliated graphite-polythiophene composite. [Brief description of the drawings]
[0018] [Figure 1] 1(a) to (c) are diagrams showing the XPS spectrum of the exfoliated graphite obtained in Example 3. [Diagram 2]2(a) to (c) are diagrams showing the XPS spectrum of the exfoliated graphite obtained in Comparative Example 1. [Diagram 3] FIG. 3 is a diagram showing Raman spectra of the exfoliated graphite obtained in Example 3 and Comparative Example 1. [Figure 4] FIG. 4 is a diagram showing the absorption spectra of the dispersions obtained in Example 2 and Comparative Example 1. [Diagram 5] FIG. 5 is a graph showing the relationship between the mass ratio (P3HT / exfoliated graphite) and the absorbance at a wavelength of 660 nm. [Figure 6] FIG. 6 is a transmission electron microscope (TEM) photograph of the cross section of the samples obtained in Examples 1 to 4 and Comparative Examples 1 and 2. [Figure 7] FIG. 7 is a diagram showing the relationship between the mass ratio (P3HT / exfoliated graphite) and the sheet resistance. [Figure 8] FIG. 8 is a diagram showing Tafel plots of the samples obtained in Example 2 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0019] The present invention will be described in detail below.
[0020] [Exfoliated graphite-polythiophene composite] The exfoliated graphite-polythiophene composite of the present invention contains exfoliated graphite and a polythiophene derivative. The exfoliated graphite is a laminate of graphene or graphene sheets.
[0021] Since the exfoliated graphite-polythiophene composite of the present invention has the above-mentioned configuration, it is difficult to be folded or curled, and has high versatility. In addition, it can effectively exhibit the inherent functions of exfoliated graphite.
[0022] Conventionally, in exfoliated graphite, alkyl aldehydes such as decanal have been used as a dispersion medium to prevent re-aggregation of graphene particles. However, alkyl aldehydes such as decanal often have biological toxicity, such as irritation to the skin and eyes, and because they are aldehydes, they are easily oxidized and have low chemical stability.
[0023] In contrast, the exfoliated graphite-polythiophene composite of the present invention contains a polythiophene derivative, and therefore can be dispersed in a wide range of solvents. Therefore, the exfoliated graphite-polythiophene composite can be dispersed in various solvents without using a dispersion medium that is toxic to the body, and is highly versatile. In addition, the exfoliated graphite-polythiophene composite is difficult to oxidize, and therefore has excellent chemical stability and can effectively exhibit the original functions of exfoliated graphite. In addition, since it contains a polythiophene derivative, the electrical conductivity can be further increased.
[0024] The present inventors have also found that by applying a coating material containing the above-mentioned exfoliated graphite-polythiophene composite to the surface of a metal, etc., corrosion on the surface of the metal, etc. can be suppressed. Therefore, the exfoliated graphite-polythiophene composite of the present invention can be suitably used as a corrosion-resistant coating material.
[0025] In the present invention, the surface of the exfoliated graphite is preferably modified with a polythiophene derivative. The polythiophene derivative may be adsorbed or grafted onto the surface of the exfoliated graphite. In this case, the exfoliated graphite can be further prevented from folding or curling. In addition, the dispersibility in a solvent or resin can be further improved, and even the addition of a small amount of exfoliated graphite can further effectively improve the mechanical properties of the resin. Whether the surface of the exfoliated graphite is modified with a polythiophene derivative can be confirmed by X-ray photoelectron spectroscopy (XPS) or Raman spectroscopy.
[0026] In the exfoliated graphite-polythiophene composite of the present invention, the ratio 2D / G, which is the peak area ratio between the 2D band and the G band in the Raman spectrum, is preferably 0.5 or more, more preferably 1.0 or more, preferably 5.0 or less, more preferably 3.0 or less, and even more preferably 2.0 or less. When the ratio 2D / G is equal to or more than the above lower limit, the number of graphene stacks in the exfoliated graphite can be further reduced. In addition, the planar structure of the exfoliated graphite can be more reliably maintained, and the exfoliated graphite can be more reliably prevented from folding or curling. When the ratio 2D / G is equal to or less than the above upper limit, physical properties such as electrical conductivity and mechanical strength of the resin can be more effectively improved.
[0027] In the present invention, the Raman spectrum is measured, for example, by a laser Raman microscope at 3100 cm -1 ~700cm -1 As the laser Raman microscope, for example, a model "LabRAM ARAMIS" manufactured by HORIBA or a model "Raman touch" manufactured by Nanophoton can be used.
[0028] The 2D band peak in the Raman spectrum is a peak derived from the number of layers, distortion, and defect structure of the graphene sheet in the exfoliated graphite. The 2D band peak is usually at 2650 cm -1 ~2750cm -1 Observed nearby.
[0029] On the other hand, the G band peak in the Raman spectrum is a peak derived from the in-plane stretching vibration of the six-membered ring structure of carbon atoms. The G band peak is usually located at 1578 cm -1 ~1592cm -1 Observed nearby.
[0030] The ratio 2D / G, which is the peak area ratio between the 2D band and the G band, is an index of the number of layers of the graphene sheets, distortion, and defect structure in the exfoliated graphite. The larger the ratio 2D / G, which is the peak area ratio between the 2D band and the G band, the smaller the number of stacked graphene sheets tends to be. In addition, with a smaller number of stacked graphene sheets, the planar structure of the exfoliated graphite can be more reliably maintained, and the exfoliated graphite can be more reliably prevented from folding or curling.
[0031] The D band peak in the Raman spectrum is a peak derived from a defect structure. The D band peak is usually located at 1345 cm -1 ~1355cm -1 Observed nearby.
[0032] The peak area ratio D / G between the D band and the G band is an index of the amount of defects in exfoliated graphite. The smaller the peak area ratio D / G between the D band and the G band, the fewer the amount of defects in exfoliated graphite.
[0033] Therefore, the exfoliated graphite-polythiophene composite of the present invention has a ratio D / G of preferably 0.8 or less, more preferably 0.5 or less. When the ratio D / G is equal to or less than the upper limit, the amount of defects in the exfoliated graphite can be further reduced, and the electrical conductivity can be further increased. The lower limit of the ratio D / G is not particularly limited, but can be, for example, 0.01.
[0034] In the present invention, the halogen content of the exfoliated graphite-polythiophene composite is preferably 1000 ppm or less, more preferably 500 ppm or less. When the halogen content of the exfoliated graphite-polythiophene composite is the above upper limit or less, the corrosion resistance can be further improved. The lower limit of the halogen content is not particularly limited, but can be, for example, 0.01 ppm.
[0035] In the present invention, the halogen content can be measured, for example, by ion chromatography.
[0036] The halogen content can be measured by ion chromatography, for example, as follows.
[0037] First, purified water is added to the exfoliated graphite-polythiophene composite, and ultrasonic treatment is performed to obtain a dispersion. The obtained dispersion is centrifuged and then filtered to obtain a filtrate, which is used as a test liquid. The obtained test liquid is subjected to measurement using an ion chromatography device to determine the halogen content. As the ion chromatography device, for example, DIONEX ICS-1500 (column: IonPac AS23A (separation column)) manufactured by Thermo Fisher Scientific can be used.
[0038] In the present invention, exfoliated graphite is obtained by exfoliating original graphite, and refers to graphene or graphene sheet laminates that are thinner than the original graphite. By adding a small amount of exfoliated graphite to a resin, the physical properties of the resin can be dramatically improved. Therefore, exfoliated graphite can be used as a so-called nanofiller.
[0039] Whether or not a graphene sheet laminate is a graphene sheet laminate can be confirmed by observing whether or not a peak (a peak derived from a graphene laminate structure) is observed around 2θ=26.4 degrees when the X-ray diffraction spectrum is measured using CuKα radiation (wavelength 1.541 Å). The X-ray diffraction spectrum can be measured by a wide-angle X-ray diffraction method. For example, SmartLab (manufactured by Rigaku Corporation) can be used as an X-ray diffraction device.
[0040] The number of stacked graphene sheets in exfoliated graphite may be less than that of the original graphite, but the number of stacked graphene sheets in exfoliated graphite is 1 or more. From the viewpoint of more effectively increasing the mechanical strength of the resin, such as the tensile modulus of elasticity, the fewer the number of stacked graphene sheets, the more desirable. Therefore, the number of stacked graphene sheets is preferably 15 layers or less, more preferably 10 layers or less.
[0041] The thickness of the exfoliated graphite is preferably 0.3 nm or more, more preferably 1 nm or more, and preferably 30 nm or less, more preferably 10 nm or less. When the thickness of the exfoliated graphite is within the above range, the mechanical strength of the resin, such as the tensile modulus of elasticity, can be more effectively increased.
[0042] The maximum dimension of the exfoliated graphite in the lamination plane direction is preferably 0.1 μm or more, more preferably 1 μm or more, preferably 200 μm or less, more preferably 100 μm or less. When the maximum dimension of the exfoliated graphite in the lamination plane direction is equal to or greater than the above lower limit, the reinforcing effect against an external force applied in a direction intersecting the lamination plane of the exfoliated graphite can be further enhanced. In addition, when the maximum dimension of the exfoliated graphite in the lamination plane direction is equal to or less than the above upper limit, when used as a reinforcing material, it is less likely to become a fracture or peeling origin due to the composite interface when filled into a matrix material (resin, metal, ceramic, etc.).
[0043] The ratio of the maximum dimension of exfoliated graphite in the lamination plane direction to the thickness of exfoliated graphite is expressed as the aspect ratio. The aspect ratio of exfoliated graphite is preferably 10 or more, more preferably 100 or more, and preferably 600,000 or less, more preferably 10,000 or less. When the aspect ratio of exfoliated graphite is equal to or more than the lower limit, the reinforcing effect against an external force applied in a direction intersecting the lamination plane of exfoliated graphite can be further enhanced. Also, when the aspect ratio of exfoliated graphite is too large, the effect becomes saturated and no further reinforcing effect can be expected.
[0044] The aspect ratio of exfoliated graphite can be determined using a scanning electron microscope photograph (SEM photograph) or the like.
[0045] Examples of polythiophene derivatives include poly(3-hexylthiophene), poly(3,4-ethylenedioxy)thiophene, and poly(3-butylthiophene). From the viewpoint of stability and conductivity, the polythiophene derivative is preferably poly(3-hexylthiophene). Poly(3-hexylthiophene) can be synthesized according to the synthesis method described in the non-patent document: S. Tamba, et al., J.Am. Chem. Sci., 133,9700 (2011).
[0046] Poly(3-hexylthiophene-2,5-diyl) is represented by the following formula (1).
[0047] [ka]
[0048] In addition, as the polythiophene derivative, other poly(3-alkylthiophenes) than poly(3-hexylthiophene) may be used. Examples of other poly(3-alkylthiophenes) include poly(3-octylthiophene). In addition, poly(3-(hexyloxy))methylthiophene may be used.
[0049] As the polythiophene derivative, a polymer having an alkyl group having a siloxane bond at the 3-position of thiophene (poly-(3-(4-pentamethyldisiloxybutan-1-yl)thiophene-2,5-diyl)) may be used.
[0050] In the present invention, the head-to-tail (hereinafter also referred to as HT) regioregularity of the polythiophene derivative is preferably 80% or more, more preferably 90% or more. Here, HT regioregularity refers to the ratio of the repeating units arranged regioregularly from head to tail.
[0051] When the HT regioregularity is equal to or higher than the above lower limit, the dispersibility of the exfoliated graphite-polythiophene composite in a solvent can be further improved.
[0052] The number average molecular weight (Mn) of the polythiophene derivative is preferably 2000 or more, more preferably 3000 or more, and even more preferably 5000 or more, and is preferably 100000 or less, more preferably 80000 or less, and even more preferably 50000 or less. When the number average molecular weight (Mn) is within the above range, the dispersibility of the exfoliated graphite-polythiophene composite in a solvent can be further improved.
[0053] In addition, the ratio of the weight average molecular weight (Mw) to the number average molecular weight (Mn), i.e., the molecular weight distribution (Mw / Mn) is preferably 1.1 or more, more preferably 1.2 or more, and preferably 1.5 or less, more preferably 1.3 or less. When the molecular weight distribution (Mw / Mn) is within the above range, the dispersibility of the exfoliated graphite-polythiophene composite in a solvent can be further improved.
[0054] The weight average molecular weight (Mw) and the number average molecular weight (Mn) indicate the weight average molecular weight (Mw) and the number average molecular weight (Mn) in terms of polystyrene measured by gel permeation chromatography (GPC).
[0055] In order to adjust the number average molecular weight (Mn) and the molecular weight distribution (Mw / Mn) to be within the above ranges, polymerization conditions such as the polymerization initiator and polymerization temperature may be adjusted.
[0056] The exfoliated graphite-polythiophene composite of the present invention may be a composite of exfoliated graphite, the surface of which is modified with a functional group derived from a compound having a carbonyl group, and a polythiophene derivative. The method for producing such an exfoliated graphite-polythiophene composite will be described in more detail in the section on the production method below.
[0057] [Method of manufacturing exfoliated graphite-polythiophene composite] The exfoliated graphite-polythiophene composite of the present invention can be obtained, for example, by a production method including the following steps 1 to 3.
[0058] (Process 1) Step 1 is a step of preparing a graphite intercalation compound (GIC) in which at least an alkali metal is intercalated between graphene layers of graphite.
[0059] Graphite is a laminate of multiple graphene sheets. The number of layers of graphene sheets in graphite is usually about 100,000 to 1,000,000. There is no particular limitation on the graphite, and appropriate raw graphite such as natural graphite or expanded graphite can be used. The expanded graphite refers to graphite in which the graphene layers are more widely spaced than in natural graphite. In expanded graphite, the graphene layers are already widely spaced, so that an alkali metal can be intercalated between the graphene layers more easily.
[0060] The alkali metal is not particularly limited, but K, Li, Na, etc. can be used. These may be used alone or in combination. It is preferable to use K or Na as the alkali metal.
[0061] The prepared GIC is preferably a ternary GIC in which an alkali metal and tetrahydrofuran (THF) are intercalated between the graphene layers. However, in the present invention, a binary GIC in which only an alkali metal is intercalated between the graphene layers may be prepared.
[0062] A ternary GIC can be obtained, for example, by dissolving an alkali metal in THF, followed by adding graphite and stirring.
[0063] The dissolution of an alkali metal in THF is preferably carried out by adding the alkali metal to a mixture of THF and an aromatic hydrocarbon. In this case, the alkali metal and the aromatic hydrocarbon form an ion pair in the mixture, so that the alkali metal can be coordinated to THF. Therefore, it becomes possible to easily dissolve an alkali metal, which is originally difficult to dissolve in THF. It is preferable to carry out this operation under an inert gas atmosphere.
[0064] Although there is no particular limitation on the THF, it is preferable to use THF that does not substantially contain dibutylhydroxytoluene (BHT) and that is sufficiently dehydrated.
[0065] The aromatic hydrocarbon is preferably a polycyclic aromatic hydrocarbon. The polycyclic aromatic hydrocarbon is not particularly limited, but may be naphthalene, phenanthrene, anthracene, or the like. These may be used alone or in combination.
[0066] The electron affinity of such aromatic hydrocarbons and graphite is significantly different. For example, the electron affinity of graphite is 1.27 eV, while that of naphthalene is -0.25 eV. Therefore, by utilizing the difference in electron affinity between graphite and aromatic hydrocarbons, it is possible to easily intercalate alkali metals coordinated to THF between graphene layers.
[0067] The inert gas is not particularly limited as long as it can block oxygen, and for example, argon gas or the like can be used.
[0068] (Process 2) Step 2 is a step in which the GIC is mixed with a compound having a carbonyl group to exfoliate the graphite and obtain exfoliated graphite.
[0069] Specifically, a liquid containing a compound having a carbonyl group is added to the GIC and stirred. If the compound having a carbonyl group is in liquid form, it can be used as the liquid as is. If the compound having a carbonyl group is in solid form, it can be used as the liquid by adding another solvent such as THF.
[0070] The compound having a carbonyl group is not particularly limited, and for example, an aldehyde derivative, a ketone derivative, or an ester derivative can be used. Among them, the compound having a carbonyl group is preferably an aldehyde derivative. In this case, the exfoliated graphite can be more reliably prevented from folding or curling.
[0071] The aldehyde derivative is not particularly limited, but examples thereof include benzaldehyde, O-phthalaldehyde, O-anisaldehyde, m-anisaldehyde, p-anisaldehyde, phthalaldehyde, 1-naphthaldehyde, 9-anthraldehyde, glucose, retinal, formaldehyde, acetaldehyde, butylaldehyde, heptanal, octanal, decanal, isovaleraldehyde, glutaraldehyde, azulene-1-carboxaldehyde, and acetoacetaldehyde dimethyl acetal. Among them, an alkyl aldehyde is preferable. An aldehyde derivative having a linear alkyl chain is preferable. Furthermore, an aldehyde derivative having a long alkyl chain is preferable. The number of carbon atoms in the linear portion of the alkyl chain is preferably 6 or more, more preferably 7 or more. In this case, it is possible to more reliably suppress folding or curling of the exfoliated graphite. The upper limit of the number of carbon atoms in the linear portion of the alkyl chain may be, for example, 20.
[0072] Examples of the ketone derivative that can be used include acetone, methyl ethyl ketone, methyl isobutyl ketone, cyclohexanone, acetylacetone, acetophenone, benzophenone, quinone, benzoquinone, and naphthoquinone.
[0073] Examples of ester derivatives that can be used include esters of organic carboxylic acids and alcohols, such as ethyl acetate, butyl acetate, butyl butyrate, 2-ethylhexyl acetate, octyl acetate, bis(2-ethylhexyl) adipate, bis(2-ethylhexyl) dodecanedioate, dioctyl phthalate, dioctyl maleate, trimethylolpropane triacetate, and pentaerythritol tetraacetate.
[0074] These compounds having a carbonyl group may be used alone or in combination of two or more kinds.
[0075] It is also preferable to carry out step 2 in an inert gas atmosphere. The inert gas is not particularly limited as long as it can block oxygen, and for example, argon gas can be used.
[0076] In step 2, a compound having an electron-withdrawing carbonyl group is added to the GIC, causing a nucleophilic addition reaction on the carbon hexagonal mesh surface of the graphite. Specifically, the compound having a carbonyl group is chemically bonded to the graphite between the graphene layers or at the graphene edge, and is grafted. Therefore, a compound having a carbonyl group larger than the original alkali metal is inserted between the graphene layers of the graphite.
[0077] When a compound having a carbonyl group larger than the original alkali metal is inserted between the graphene layers, graphite is exfoliated. This allows exfoliated graphite to be obtained. At least a part of the surface of the obtained exfoliated graphite can be coated with the compound having a carbonyl group by grafting or the like.
[0078] (Step 3) Step 3 is a step of compounding the exfoliated graphite with a polythiophene derivative.
[0079] First, in step 2, when the compound having a carbonyl group is liquid, exfoliated graphite is dispersed in the liquid compound having a carbonyl group to obtain an exfoliated graphite dispersion. When the compound having a carbonyl group is solid, exfoliated graphite is dispersed in another solvent such as THF to obtain an exfoliated graphite dispersion. Hereinafter, an exfoliated graphite dispersion in which exfoliated graphite is dispersed in a liquid compound having a carbonyl group is used.
[0080] Next, the polythiophene derivative is dissolved in a solvent to obtain a polythiophene derivative solution. The solvent for dissolving the polythiophene derivative may be toluene, THF, or the like.
[0081] Next, the exfoliated graphite dispersion liquid and the polythiophene derivative solution are mixed. As a result, the exfoliated graphite and the polythiophene derivative are composited to obtain an exfoliated graphite-polythiophene composite. In addition, when the exfoliated graphite and the polythiophene derivative are composited, for example, ultrasonic treatment, heating, a homogenizer, or other means can be used.
[0082] In this case, the mass ratio of the polythiophene derivative to the exfoliated graphite (polythiophene derivative / exfoliated graphite) is preferably 5 or more, more preferably 8 or more, and preferably 50 or less, more preferably 20 or less. When the mass ratio (polythiophene derivative / exfoliated graphite) is equal to or more than the lower limit, folding or curling can be more effectively suppressed. When the mass ratio (polythiophene derivative / exfoliated graphite) is equal to or less than the upper limit, the inherent functions of the exfoliated graphite, such as electrical conductivity, can be more effectively exhibited.
[0083] It is preferable to replace the compound (solvent) having a carbonyl group with an alcohol such as methanol, ethanol, or benzyl alcohol, and then disperse the compound in the solvent. For example, alcohol is added to the exfoliated graphite-polythiophene composite dispersion and allowed to stand, and then the supernatant is collected and alcohol is added again. This operation is repeated several times, and finally the alcohol is distilled off to disperse the compound in the solvent. As the solvent after replacement, toluene, THF, etc. can be used.
[0084] As described above, when the compound (solvent) having a carbonyl group is replaced via a process of replacing with an alcohol such as methanol, the loss of the exfoliated graphite-polythiophene composite during the replacement operation can be reduced.
[0085] In the obtained exfoliated graphite-polythiophene composite, exfoliated graphite and a polythiophene derivative are composited, so that restacking of the obtained exfoliated graphite is even less likely to occur, making it possible to efficiently obtain exfoliated graphite with an even smaller number of layers.
[0086] In addition, since the exfoliated graphite and the polythiophene derivative are composited, the obtained exfoliated graphite can maintain a planar structure and can suppress folding or curling of the exfoliated graphite. Therefore, by adding it to a resin, the physical properties such as the mechanical strength of the resin can be further improved. In addition, when used as an electrode material, a conductive path is easily formed. Furthermore, it is also easy to handle.
[0087] In addition, the present production method does not involve a process of oxidizing graphite. Therefore, the exfoliated graphite constituting the obtained exfoliated graphite-polythiophene composite has few defects and a low degree of oxidation. Therefore, the obtained exfoliated graphite-polythiophene composite has excellent flame retardancy, electrical conductivity, or thermal conductivity.
[0088] In addition, in this production method, compounds containing halogens, such as organic halogen compounds, are not actively used. Therefore, the halogen content of the obtained exfoliated graphite-polythiophene composite can be reduced. Therefore, when the obtained exfoliated graphite-polythiophene composite is used to cover a metal surface, corrosion of the metal can be further suppressed.
[0089] Furthermore, this production method is highly versatile because it allows dispersion in various solvents such as toluene without using a dispersion medium that is toxic to living organisms.
[0090] [Corrosion-resistant coating material] The corrosion-resistant coating material of the present invention is a coating material that can suppress corrosion of a metal surface by applying it to the surface of a metal, etc. Such a corrosion-resistant coating material of the present invention contains the above-mentioned exfoliated graphite-polythiophene composite and, if necessary, a solvent.
[0091] The content of the exfoliated graphite-polythiophene composite is not particularly limited, but is preferably 1% by mass or more, more preferably 3% by mass or more, and preferably 50% by mass or less, more preferably 30% by mass or less, based on the entire corrosion-resistant coating material. When the content of the exfoliated graphite-polythiophene composite is equal to or more than the above lower limit, corrosion of the metal surface can be further suppressed when the coating is applied to the surface of a metal or the like. When the content of the exfoliated graphite-polythiophene composite is equal to or less than the above upper limit, the coatability of the corrosion-resistant coating material can be further improved.
[0092] The solvent is not particularly limited, and for example, toluene, THF, etc. can be used.
[0093] The corrosion-resistant coating material of the present invention may also contain other additives. The other additives are not particularly limited, and examples thereof include antioxidants such as phenols, phosphorus, amines, or sulfurs, ultraviolet absorbers such as benzotriazoles or hydroxyphenyltriazines, metal damage inhibitors, halogenated flame retardants such as hexabromobiphenyl ether or decabromodiphenyl ether, flame retardants such as ammonium polyphosphate or trimethyl phosphate, inorganic fillers such as calcium carbonate, talc, mica, clay, aerosil, silica, aluminum hydroxide, magnesium hydroxide, and silica sand, antistatic agents, stabilizers, pigments, dyes, and binder resins. These additives may be used alone or in combination.
[0094] The present invention will now be described in more detail with reference to specific examples and comparative examples, although the present invention is not limited to the following examples.
[0095] Examples and Comparative Examples Fabrication of GICs; The glove box was filled with argon gas (argon gas 99.999% or more, dew point -80°C or less) and diluted with THF 20×10 -3 dm 3 To the mixture, 1.5 g of naphthalene and 0.5 g of potassium were added to prepare a mixed solution. The prepared mixed solution was stirred for 30 minutes at 200 rpm using a stirrer. After stirring, 0.5 g of natural graphite powder (manufactured by SEC Carbon, grade: SN-100, average particle size 100 μm) was added. Then, the mixture was stirred again at 200 rpm for one day using a stirrer. After stirring, the obtained mixed solution was filtered in a glove box under an argon gas atmosphere to separate K-THF-GIC in which potassium (K) and THF were intercalated. The obtained K-THF-GIC was dissolved in 20×10 THF and filtered to obtain K-THF-GIC. -3 dm 3 The K-THF-GIC was washed by repeating the process of immersion in and filtration twice. After washing, the K-THF-GIC was deep blue in color.
[0096] Preparation of exfoliated graphite; After washing, 0.05 g of the obtained K-THF-GIC was placed in a sample bottle in a glove box under an argon gas atmosphere. Then, 5.5 × 10 decanal was added to the sample bottle. -2 mol was added and stirred at room temperature at 100 rpm for 72 hours using a stirrer. After that, it was left to stand for 5 minutes, separated into a supernatant and a precipitate, and the obtained supernatant was centrifuged at 15,000 rpm for 15 minutes to remove decanal, and the precipitate was collected. 10 mL of THF was added to the obtained precipitate, and centrifuged at 15,000 rpm for 15 minutes to collect the precipitate. The same operation was performed again to obtain a precipitate from which unreacted decanal had been washed. Furthermore, 10 mL of ion-exchanged water was added to the obtained precipitate, and centrifuged at 15,000 rpm for 15 minutes to obtain exfoliated graphite. The obtained exfoliated graphite had a surface covered with decanal.
[0097] Decanal was added to the obtained exfoliated graphite to obtain an exfoliated graphite dispersion with an exfoliated graphite concentration of 10 μg / mL. Meanwhile, toluene was added to poly(3-hexylthiophene) (P3HT, number average molecular weight: 10000) to obtain P3HT solutions with concentrations of 0 μg / mL, 50 μg / mL, 100 μg / mL, 200 μg / mL, and 400 μg / mL. 1 mL of each P3HT solution was added to 1 mL of exfoliated graphite dispersion in separate vials. As a result, samples with mass ratios of P3HT to exfoliated graphite (P3HT / exfoliated graphite) of 0, 5, 10, 20, and 40 were prepared, respectively. The sample with a mass ratio (P3HT / exfoliated graphite) of 0 was designated as Comparative Example 1, the sample with a mass ratio of 5 was designated as Example 1, the sample with a mass ratio of 10 was designated as Example 2, the sample with a mass ratio of 20 was designated as Example 3, and the sample with a mass ratio of 40 was designated as Example 4.
[0098] 2 mL of each sample was subjected to ultrasonic treatment (apparatus: AS ONE Corporation, product number "VS-D100") for 30 minutes at room temperature (25°C) and 31 kHz. After treatment, 6 mL of methanol was added and left to stand for 23 hours. After standing, 6 mL of the supernatant was collected and the same amount of methanol was added. Then, the mixture was stirred for 10 seconds and subjected to ultrasonic treatment (apparatus: AS ONE Corporation, product number "VS-D100") for 5 minutes at room temperature (25°C) and 31 kHz. After the first ultrasonic treatment, the above operation from adding methanol to ultrasonic treatment was repeated four times. Note that in the fourth time, methanol was not added after collecting the supernatant. Next, the mixture was vacuum dried overnight (15 hours) to distill off the methanol (the operation up to this point is called the decanal removal operation).
[0099] [evaluation] (Evaluation by X-ray photoelectron spectroscopy) Toluene (2 mL) was added to 0.002 g of a sample obtained by carrying out the decanal removal operation in Example 3 and Comparative Example 1 on a scale 10 times larger than that described above. After the addition of toluene, ultrasonic treatment was performed for 30 minutes at room temperature (25°C) and 31 kHz (apparatus: AS ONE Corporation, product number "VS-D100"). Next, the sample was heated at 60°C for 10 minutes using a hot plate. Next, 1.8 mL of the dispersion was suction filtered using a filter paper with a diameter of 8 mm, and dried at 100°C for 20 minutes using a hot plate. Finally, the sample was vacuum dried at 25°C for 1 hour. The exfoliated graphite on the filter paper was measured by X-ray photoelectron spectroscopy (XPS) using an X-ray photoelectron spectrometer (ULVAC-PHI Corporation, product number "PHI X-tool").
[0100] Figures 1(a) to (c) are diagrams showing XPS spectra of exfoliated graphite obtained in Example 3. Also, Figures 2(a) to (c) are diagrams showing XPS spectra of exfoliated graphite obtained in Comparative Example 1. In Figures 1 and 2, (a) shows a spectrum in the range of binding energy from 0 eV to 1000 eV. Also, (b) shows an enlarged view of the O1s peak in (a), and (c) shows an enlarged view of the S2p peak in (a).
[0101] 1 and 2, a peak of S derived from the polythiophene derivative was observed in Example 3, whereas no peak of S was observed in Comparative Example 1. From this, it was confirmed that a composite in which the polythiophene derivative was present on the surface of the exfoliated graphite was obtained in Example 3.
[0102] (Evaluation by Raman spectroscopy) Toluene (2 mL) was added to 0.002 g of a sample obtained by carrying out the decanal removal operation in Example 3 and Comparative Example 1 on a scale 10 times larger than that described above. After the addition of toluene, ultrasonic treatment was performed for 30 minutes at room temperature (25°C) and 31 kHz (apparatus: AS ONE Corporation, product number "VS-D100"). Next, the sample was heated at 60°C for 10 minutes using a hot plate. Next, 1.8 mL of the dispersion was suction filtered using a filter paper with a diameter of 8 mm, and dried at 100°C for 20 minutes using a hot plate. Finally, the sample was vacuum dried at 25°C for 1 hour. For the exfoliated graphite on the filter paper, imaging Raman was measured by Raman spectroscopy using a microscopic laser Raman spectrometer (JASCO Corporation, product number "NRS-7100") with a laser: 532 nm.
[0103] 3 is a diagram showing the Raman spectra of the exfoliated graphite obtained in Example 3 and Comparative Example 1. As shown in FIG. 3, in Example 3 and Comparative Example 1, the D band (1350 cm -1 ) was not observed, it can be seen that there are almost no defects on the graphene plane. In addition, the position of the G band and the shape of the 2D band can confirm the structure derived from exfoliated graphite. Furthermore, in Example 3, a peak at 1448 cm that cannot be confirmed in Comparative Example 1 was observed. -1 A peak derived from P3HT was observed around 1000 nm. This also confirmed that a composite in which a polythiophene derivative was present on the surface of exfoliated graphite was obtained in Example 3.
[0104] Similarly, in Examples 1, 2, and 4, it was confirmed by XPS and Raman spectroscopy that a composite in which a polythiophene derivative was present on the surface of exfoliated graphite was obtained.
[0105] (Evaluation of Absorption Spectrum) In Examples 1 to 4 and Comparative Example 1, 1 mL of toluene was added after the decanal removal operation. After the addition of toluene, ultrasonic treatment (apparatus: AS ONE Corporation, product number "VS-D100") was performed for 30 minutes under conditions of room temperature (25°C) and 31 kHz. Thereafter, the mixture was heated at 60°C for 10 minutes to obtain a dispersion liquid.
[0106] Fig. 4 is a diagram showing the absorption spectra of the dispersions obtained in Example 2 and Comparative Example 1. Also, Fig. 5 is a diagram showing the relationship between the mass ratio (P3HT / exfoliated graphite) and the absorbance at a wavelength of 660 nm.
[0107] As shown in FIG. 4, P3HT exhibits absorbance in the wavelength region of 600 nm or less, whereas graphene exhibits absorbance in the entire wavelength region of 300 nm to 800 nm. Therefore, as shown in FIG. 5, by focusing on the absorbance at a wavelength of 660 nm, it is possible to confirm the absorbance originating only from graphene. In addition, since the absorbance of graphene increases as the degree of exfoliation of graphene increases, it can be seen from the graph shown in FIG. 5 that the degree of exfoliation of graphene increases as the amount of P3HT added increases. Therefore, it can be confirmed that the restacking of graphene is suppressed by the addition of P3HT.
[0108] (TEM observation) In Examples 1 to 4 and Comparative Example 1, after the decanal removal operation, 1 mL of toluene was added. After the addition of toluene, ultrasonic treatment was performed for 30 minutes at room temperature (25°C) and 31 kHz (apparatus: AS ONE Corporation, product number "VS-D100"). Then, the mixture was heated at 60°C for 10 minutes to obtain a dispersion. 2.5 μL of the obtained dispersion was dropped onto a microgrid and dried overnight (15 hours) to distill off the toluene.
[0109] In addition, as Comparative Example 2, a dispersion before the decanal removal operation, i.e., an exfoliated graphite dispersion obtained by adding decanal to exfoliated graphite, was used. 2.5 μL of the obtained dispersion was dropped onto a microgrid and vacuum-dried overnight (15 hours) at 200 ° C. using a vacuum oven. Next, the decanal was distilled off by drying in a freeze dryer.
[0110] Fig. 6 is a transmission electron microscope (TEM) photograph of the cross section of the samples obtained in Examples 1 to 4 and Comparative Examples 1 and 2. The TEM photograph in Fig. 6 was measured using a transmission electron microscope (manufactured by JEOL Ltd., product number: JEM-2100F). It was confirmed from Fig. 6 that the samples obtained in Examples 1 to 4 and Comparative Example 2 were not folded or curled, and were flat. On the other hand, the sample obtained in Comparative Example 1 was folded or curled.
[0111] (Evaluation of electrical conductivity) Toluene (2 mL) was added to 0.002 g of a sample obtained by carrying out the decanal removal operation in Examples 1 to 4 and Comparative Example 1 on a scale 10 times larger than that described above. After the addition of toluene, ultrasonic treatment (apparatus: AS ONE Corporation, product number "VS-D100") was performed for 30 minutes at room temperature (25°C) and 31 kHz. Next, the sample was heated at 60°C for 10 minutes using a hot plate. Next, 1.8 mL of the dispersion was suction filtered using a filter paper with a diameter of 8 mm, and dried at 100°C for 20 minutes using a hot plate. Finally, the sample was vacuum dried at 25°C for 1 hour. The electrical resistivity of the obtained sample was measured at four points using a four-terminal resistance meter (Mitsubishi Chemical Analytech Co., Ltd., product number "Loresta-AX").
[0112] Fig. 7 is a diagram showing the relationship between the mass ratio (P3HT / exfoliated graphite) and the sheet resistance. As shown in Fig. 7, the sheet resistance value increased as the mass ratio (P3HT / exfoliated graphite) increased, but was at a level where electrical conduction could be confirmed in an electrical conduction test. On the other hand, in the case of a sample of P3HT itself, the sheet resistance value was higher than the measurement limit, and electrical conduction could not be confirmed in an electrical conduction test.
[0113] (Corrosion resistance evaluation) 333 μL of toluene was added to 0.0002 g of the sample obtained by performing the decanal removal operation in Example 2 and Comparative Example 1. After the addition of toluene, ultrasonic treatment was performed for 30 minutes under conditions of room temperature (25° C.) and 31 kHz (apparatus: AS ONE Corporation, product number "VS-D100"). Next, the sample was heated at 60° C. for 10 minutes using a hot plate to obtain a dispersion liquid as a sample.
[0114] Next, the copper foil (10 mm x 20 mm) was wiped with ethanol and then immersed in 0.1 M hydrochloric acid at room temperature (25°C) for 10 minutes. It was washed three times each with excess water and ethanol, and then vacuum dried for one hour. Thereafter, it was masked with tape (window shape: circle with a diameter of 5 mm) to obtain a copper foil substrate.
[0115] Next, the above dispersion liquid as a sample was dropped twice at 10 μL onto the above copper foil substrate, and then vacuum dried overnight (15 hours). For comparison, a solution (33 μg / mL) of P3HT dispersed in toluene was also dropped twice at 10 μL onto the above copper foil substrate, and then vacuum dried overnight (15 hours).
[0116] Next, the corrosion potential and the corrosion current were measured by Cyclic Voltammetry (CV) (apparatus: Bio-logic Science Instruments, product number "VMP3") at a potential sweep rate of 5 mV / s.
[0117] Fig. 8 is a diagram showing the Tafel plots of the samples obtained in Example 2 and Comparative Example 1. As shown in Fig. 8, the sample obtained in Example 2 had the smallest valley peak of the corrosion current value, and it was confirmed that the corrosion of the copper foil surface was suppressed. Similarly, it was confirmed that the samples obtained in Examples 1, 3 to 4 also had the corrosion of the copper foil surface suppressed.
Claims
1. An exfoliated graphite-polythiophene composite, comprising exfoliated graphite, the surface of which is modified with functional groups derived from an alkylaldehyde and which is a laminate of graphene or graphene sheets, and a polythiophene derivative.
2. 2. The exfoliated graphite-polythiophene composite according to claim 1, wherein the polythiophene derivative is poly(3-hexylthiophene).
3. The exfoliated graphite-polythiophene composite according to claim 1 or 2, wherein the number of stacked graphene sheets in the exfoliated graphite is 1 or more and 15 or less.
4. A method for producing the exfoliated graphite-polythiophene composite according to any one of claims 1 to 3, comprising the steps of: preparing a graphite intercalation compound in which at least an alkali metal is intercalated between graphene layers of graphite; a step of exfoliating the graphite by mixing the graphite intercalation compound with an alkylaldehyde to obtain exfoliated graphite; A step of compounding the exfoliated graphite with a polythiophene derivative; A method for producing an exfoliated graphite-polythiophene composite comprising the steps of:
5. A corrosion-resistant coating material comprising the exfoliated graphite-polythiophene composite according to any one of claims 1 to 3.
Citation Information
Patent Citations
Composite material, conductive material, conductive particles, and conductive film
WO2017145940A1
Flake graphite and manufacturing method therefor
WO2020175504A1